Effect of hot water treatment on peach volatile emission and Monilinia fructicola development. (6th March 2015) - Spadoni, A.; Cappellin, L.; Neri, F.; Algarra Alarcon, A.; Romano, A.; Guidarelli, M.; Gasperi, F.; Biasioli, F.; Mari, M.
Abstract : The effect of hot water treatment (HWT) to control peach brown rot was investigated. Peaches were dipped in water at 60°C for 60 s and artificially inoculated with Monilinia fructicola conidia. HWT failed to control brown rot if applied before inoculation and microscopic observations revealed a stimulatory effect on germ tube elongation of M. fructicola conidia placed immediately after HWT on the fruit surface, compared to the control. The influence of fruit volatile emission due to HWT was performed on the pathogen conidia exposed to the headspace surrounding peaches. The results showed an increase of M. fructicola conidial germination ranging from 33 to 64% for cultivars Lucie Tardibelle and Red Haven heat‐treated peaches, respectively, compared to the control. The volatile blend emitted from heat‐treated fruit was analysed by solid‐phase microextraction/gas chromatography‐mass spectrometry (SPME/GC‐MS) and proton transfer reaction‐time of flight‐mass spectrometry (PTR‐ToF‐MS). Fifty compounds were detected by SPME/GC‐MS in volatile blends of cv. Lucie Tardibelle peaches and significant differences in volatile emission were observed among heated and control fruit. Using PTR‐ToF‐MS analysis, acetaldehyde and ethanol were detected at levels 15‐ and 28‐fold higher in heated fruit compared to unheated ones, respectively. In vitro assays confirmed the stimulatory effect (60 and 15%) of acetaldehyde (0·6 μL L −1 ) and ethanol (0·2 μL L −1 ) on M. fructicola conidial germination and mycelial growth, respectively. The results showed that volatile organic compounds (VOCs) emitted from heat‐treated peaches could stimulate M. fructicola conidial germination, increasing brown rot incidence in treated peaches when the inoculation occurs immediately after HWT.